Structural Determinants of Health among Im/Migrants in the Indoor Sex Industry: Experiences of Workers and Managers/Owners in Metropolitan Vancouver. - Shira M Goldenberg; Andrea Krüsi; Emma Zhang; Jill Chettiar; Kate Shannon (PLoS ONE)
Background Globally, im/migrant women are overrepresented in the sex industry and experience disproportionate health inequities. Despite evidence that the health impacts of migration may vary according to the timing and stage of migration (e.g., early arrival vs. long-term migration), limited evidence exists regarding social and structural determinants of health across different stages of migration, especially among im/migrants engaged in sex work. Our aim was to describe and analyze the evolving social and structural determinants of health and safety across the arrival and settlement process for im/migrants in the indoor sex industry. Methods We analyzed qualitative interviews conducted with 44 im/migrant sex workers and managers/owners working in indoor sex establishments (e.g., massage parlours, micro-brothels) in Metropolitan Vancouver, Canada in 2011; quantitative data from AESHA, a larger community-based cohort, were used to describe socio-demographic and social and structural characteristics of im/migrant sex workers. Results Based on quantitative data among 198 im/migrant workers in AESHA, 78.3% were Chinese-born, the median duration in Canada was 6 years, and most (86.4%) serviced clients in formal indoor establishments. Qualitative narratives revealed diverse pathways into sex work upon arrival to Canada, including language barriers to conventional labour markets and the higher pay and relative flexibility of sex work. Once engaged in sex work, fear associated with police raids (e.g., immigration concerns, sex work disclosure) and language barriers to sexual negotiation and health, social and legal supports posed pervasive challenges to health, safety and human rights during long-term settlement in Canada. Conclusions Findings highlight the critical influences of criminalization, language barriers, and stigma and discrimination related to sex work and im/migrant status in shaping occupational health and safety for im/migrants engaged in sex work. Interventions and policy reforms that emphasize human rights and occupational health are needed to promote health and wellbeing across the arrival and settlement process.